Adsorptive characterization of the ZIF-68 metal-organic framework: a complex structure with amphiphilic properties - Van der Perre, Stijn; Van Assche, Tom; Bozbiyik, Belgin; Lannoeye, Jeroen; De Vos, Dirk E; Baron, Gino V; Denayer, Joeri F M (Langmuir, 2014)
In this experimental study, the adsorption behavior of the ZIF-68 heterolinked zeolitic imidazolate framework has been explored. Vapor phase adsorption isotherms of linear C1-C6 alcohols, C6 alkane isomers, aromatics (benzene, toluene, xylene isomers, 1,3,5-trimethylbenzene, and 1,3,5-triisopropylbenzene), and polar adsorbates (water, acetonitrile, and acetone) are reported and discussed. The complex pore structure of ZIF-68, with two one-dimensional channels, each with a different polarity, displays an overall hydrophobic character. Its two-pore system results in S-shaped isotherms for small polar adsorbates (small alcohols, acetone, and acetonitrile), while longer alcohols and nonpolar molecules, such as aromatics and C6 alkane isomers, lead to type I adsorption isotherms. Bulky molecules, with a kinetic diameter significantly larger than the pore windows, are adsorbed in large amounts, which gave reason to think that this ZIF-68 material has a certain degree of framework flexibility to enlarge the free aperture of the channels. Besides, diffusion coefficients from vapor phase uptake and infrared experiments point to a different adsorption mechanism for polar and nonpolar adsorbates. Liquid phase adsorption experiments demonstrated the separation of alcohol mixtures (ethanol/1-butanol) at low concentration from water, with a clear preference for 1-butanol.